Relocation and Focal Mechanism of Aftershocks Pidie Jaya Earthquake (Mw6.5) Dec 7th, 2016 using BMKG Network - Pepen Supendi; Andri D. Nugraha; Tony Agus Wijaya (Himpunan Ahli Geofisika Indonesia (HAGI), 2017)
We have successfully relocated 74 out of 89 aftershocks until December 19, 2016, by using hypocenter double-difference method. We also have conducted focal mechanism analysis to estimate the type of fault slip. The results indicate improvement in hypocenter location, where the initial earthquakes focus depth at a fixed depth of 10 km have been updated and have described the patterns of active fault in the area trending Northwest-Southeast. The validity through the histogram of travel-time residual shows fairly good data processing where the residual value is close to zero (t.obs - t.cal 0). Based on focal mechanism solutions of mainshock and two selected aftershocks, the type of fault is right lateral strike-slip.